2022
DOI: 10.1089/jpm.2021.0490
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Understanding of Preferences and Values of People with Hematological Malignancies at the End of Life: Concurrent Surveys

Abstract: Background: People with hematological malignancies can deteriorate rapidly to a terminal event and have variable levels of engagement when transitioning to palliative and end-of-life care. Objectives: To describe end-of-life care values and preferences of people with hematological malignancies and explore whether these align with hematology clinicians' perceptions. Design: Two matched anonymous quantitative cross-sectional surveys explored: 1) patients' values and preferences around manner and timing of discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Completing the AD statement and LST documentation helps clinicians provide goal‐aligned care for patients 34 . Patients with HM want an honest prognosis and communication from medical professionals, 35 but ACP in this population is difficult owing to challenges in determining the correct timing, barriers to clinician‐patient communication, and challenges in the documentation 36 . PC consultation can facilitate relevant discussions about EOL care among patients, family members, and primary physicians who may feel uncomfortable initiating these discussions 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Completing the AD statement and LST documentation helps clinicians provide goal‐aligned care for patients 34 . Patients with HM want an honest prognosis and communication from medical professionals, 35 but ACP in this population is difficult owing to challenges in determining the correct timing, barriers to clinician‐patient communication, and challenges in the documentation 36 . PC consultation can facilitate relevant discussions about EOL care among patients, family members, and primary physicians who may feel uncomfortable initiating these discussions 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have consistently shown that majorities of patients prefer to receive accurate and honest prognostic information, [33,57] including average and best-case survival outcomes [58]. However, this is not universal: there is considerable variation in how much prognostic information patients and caregivers wish to receive [13,59].…”
Section: Prognostic Communication Techniquesmentioning
confidence: 99%